Systemic amyloidosis with bilateral conjunctival involvement: a case report - Correa, Leandro Javier (2015)
Conjunctival amyloidosis is a very rare condition, generally unilateral, and presents mostly as an isolated condition without systemic compromise. Our purpose is to present a new case of systemic amyloidosis with a bilateral conjunctival involvement.